Analysis of hydrolytic differences of free and polyacrylic acid (PAAc)-conjugated trypsin and chymotrypsin by using fluorescence lifetime distributions - Polat, Ummugulsum; Ozyigit, Ibrahim Ethem; Karakus, Emine (TAYLOR & FRANCIS INC, 2020)
Electroanalytic, photometric or fluorometric methods may provide information about the presence of proteolysis in a related sample, but they cannot accurately identify which protease belongs to the proteolytic activity. In other words, they cannot distinguish the proteases according to the differences in their activities. Previous studies on the chymotrypsin and trypsin have shown that the activities of proteases can be distinguished from each other by fluorescence lifetime distributions. In this study, it is aimed to show the sensitivity of the distributional model on the proteolytic activities of the two proteases. For this purpose, the proteolytic activities have been reduced by making covalent conjugation with polyacrylic acid (PAAc) and the effects of the low activities were examined on Bovine Serum Albumin (BSA) which excimer emission character was incorporated into its structure by modification with N-(1-pyrenyl)maleimide. The time-resolved spectrofluorometer was used to collect fluorescence decay data at lambda(excimer) = 464 nm, which were analyzed by using Exponential Series Method (ESM) to obtain the changes of lifetime distributions. The results showed a significant decline in the activities. Despite the very low activities, the changes of fluorescence lifetime distributions exhibited remarkable specific differences that proved the sensitivity of ESM analysis.
Keywords: Bovine serum albumin; chymotrypsin; excimer; fluorescence lifetime distribution; low activities; N-(1-pyrenyl) maleimide; polyacrylic acid; trypsin; N-(1-PYRENE)MALEIMIDE; RECOVERY; CARBOMER; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology